Gambling Harm as a Global Public Health Concern: A Mixed Method Investigation of Trends in Wales - John, Bev; Holloway, Katy; Davies, Nyle; May, Tom; Buhociu, Marian; Cousins, Alecia L.; Thomas, Samantha; Roderique-Davies, Gareth (Frontiers in Public Health, 2020)
Background: Recent research evidence has suggested that gambling is a public health concern. A number of studies report the association between gambling activity and increased instances of various other harms, including substance misuse and psychological disorders. In parallel to alcohol misuse, it is also becoming clear that gambling related harm is more of a continuum of harm, as opposed to traditionally accepted categorisations of gambling behavior: safe and responsible or “problem” and harmful. Previous effective treatment models for alcohol misuse have considered a public health approach to develop interventions. As such, the current research seeks to use a public health approach to both investigate the extent of gambling harm across Wales, and to identify upstream predictors of harm to inform future interventions. Method: A triangulation of data collection methods was utilized across Wales, UK. Two hundred and forty-eight participants completed a quantitative survey relating to gambling behavior and related harm, which included the Problem Severity Gambling Index, the Gambling Commission measure of frequency, The Gambling Motives Questionnaire and the Fast Alcohol Screening tool. Ninety-eight of these participants completed a qualitative subsection. Structured interviews were conducted with 20 individuals from 11 service providers. Semi-structured interviews were conducted for the five case studies of individuals who had previously sought help for gambling. The geographical density and distribution of Licensed Gambling Outlets was also mapped in local areas. Results: The findings provide further evidence of a continuum of gambling related harm. Twenty seven percent of survey participants demonstrate some indicators of risk of gambling harm. Social, cultural and environmental contexts play a role in initiation and maintenance of gambling behavior and the subsequent related harm. Accounts from individuals corroborated the quantitative findings. Conclusions: Findings from this Welsh sample are in line with and add support to the growing international research evidence that gambling harms are a universal issue that cross cultures. It is clear that action is needed by legislators at a policy level and that broadening the focus of intervention to a public health level is necessary to develop effective strategies for harm reduction.